2019
DOI: 10.3847/1538-4357/ab09ec
|View full text |Cite
|
Sign up to set email alerts
|

Weak Shock Propagation with Accretion. II. Stability of Self-similar Solutions to Radial Perturbations

Abstract: Coughlin et al. (2018b) (Paper I) derived and analyzed a new regime of self-similarity that describes weak shocks (Mach number of order unity) in the gravitational field of a point mass. These solutions are relevant to low energy explosions, including failed supernovae. In this paper, we develop a formalism for analyzing the stability of shocks to radial perturbations, and we demonstrate that the self-similar solutions of Paper I are extremely weakly unstable to such radial perturbations. Specifically, we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Panel (a) shows that ṁ is predicted extremely well and serves as independent confirmation of the Coughlin et al (2019) rarefaction wave solutions. While there are some small differences between the two curves in panels (b)-(d), the magnitude and direction angles of j acc are well-predicted using the mean profiles and the assumption of ballistic infall from rest.…”
Section: Comparison To Semi-analytical Predictionsmentioning
confidence: 64%
See 2 more Smart Citations
“…Panel (a) shows that ṁ is predicted extremely well and serves as independent confirmation of the Coughlin et al (2019) rarefaction wave solutions. While there are some small differences between the two curves in panels (b)-(d), the magnitude and direction angles of j acc are well-predicted using the mean profiles and the assumption of ballistic infall from rest.…”
Section: Comparison To Semi-analytical Predictionsmentioning
confidence: 64%
“…There is, in fact, a small pressure gradient behind the rarefaction wave (Coughlin et al 2019), so the time for the shell to fall back after the arrival of the rarefaction wave is actually 1.14 t ff (r) for our simulated values of b and γ (E. R. Coughlin, private communication). The total time required for the shell at r to reach the sink is thus tacc(r) = 1.14 t ff (r) + twave(r).…”
Section: Data Availabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…Our models assumed a point explosion at the centre of the star, but different energy injection mechanisms (such as the outward expansion during a failed SN, Coughlin et al 2018b, or spatially extended wave heating in a stellar envelope) can allow for the self-similar solution to arise. As discussed in Coughlin et al (2019) and Ro et al (2019), despite being weakly unstable, their self-similar solution is likely to prevail in the envelopes of supergiants where density scales as ρ ∝ r −n over several orders of magnitude. As the weak shock approaches the stellar surface, it eventually transitions to a strong shock and starts accelerating, as dictated by the GFKS solution.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 95%
“…The propagation of weak shocks in stellar envelopes has been studied analytically by Coughlin et al (2018), who found a selfsimilar solution describing the propagation of a spherical weak shock wave in a hydrostatic medium with a point mass gravitational field, and later analyzed the solution's stability in Coughlin et al (2019) and Ro et al (2019). Their solution exists when the density scales as 𝜌 ∝ 𝑟 −𝑛 , where 2 < 𝑛 < 3.5, with the shock propagating with a constant and order-unity Mach number, 𝑣 sh = 𝑉 √︁ 𝐺 𝑀 0 /𝑟, where 𝑉 (𝑛) 1 is a constant and 𝑀 0 is the point mass dominating the gravitational field.…”
Section: Discussionmentioning
confidence: 99%